O constitucionalismo do porvir e a sociedade aberta de intérpretes constitucionais - Cleyson de Moraes Mello; Thiago Moreira (Revista Interdisciplinar de Direito, 2014)
This paper aims to demonstrate in brief exposure to hermeneutical theory propagated by Peter Häberle, german constitutionalist, author of the theory of the open society of constitutional interpreters, and its contribution to legal science, notedly with respect to constitutional interpretation. Will be given emphasis to its infl uence on the understanding of what we call the democratic rule of law, will be studied the participation and the social legitimacy for the maintenance and advancement of eff ective and effi cient constitutional interpretation giving greater legitimacy to judicial decisions, and, also, study the ways in which constitutional interpreters, in this context understood as an open society of interpreters, promove the advance in the quest to provide eff ectiveness of constitutional values.